2014
DOI: 10.1177/0969733014534872
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Brazilian nursing professionals

Abstract: There is a lack of empathy studies in professional practice contexts, in human resource development programs, and throughout the professional education process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
0
19
1
8
Order By: Relevance
“…선행연구에 따르면 공감능력은 대인관계를 긍정적으로 유지해주는 수단이 될 뿐 아니라 [5] 임상수행능력에도 긍정적인 영향을 주는 것으로 보 고되고 있다 [6]. 간호영역에서 공감능력에 대한 대부분의 기존 연구는 간호학생에 초점을 맞추고 있으며 [6,7], 최근에는 임상 현장에서 근무하는 간호사의 공감능력에 관해서도 연구되고 있지만 [8] …”
Section: 공감이란 당사자들이 서로 공유 가능한 의도를 함께 만들어 가는 소통 순환과정으로 노인을 돌보는 간호 제공자들unclassified
“…선행연구에 따르면 공감능력은 대인관계를 긍정적으로 유지해주는 수단이 될 뿐 아니라 [5] 임상수행능력에도 긍정적인 영향을 주는 것으로 보 고되고 있다 [6]. 간호영역에서 공감능력에 대한 대부분의 기존 연구는 간호학생에 초점을 맞추고 있으며 [6,7], 최근에는 임상 현장에서 근무하는 간호사의 공감능력에 관해서도 연구되고 있지만 [8] …”
Section: 공감이란 당사자들이 서로 공유 가능한 의도를 함께 만들어 가는 소통 순환과정으로 노인을 돌보는 간호 제공자들unclassified
“…Arguably, the reason for increasing level of empathy with increasing age may be related to growing life experience [56]. It was contrary to Trevizan and colleagues' study [57], who did not find any effect of age on the level of Brazilian nurses' empathy. In parallel to our finding, the results of a cross-sectional study in different health professions in two Australian universities showed that 26-30 years old and 31-35 years old students had higher empathy scores by the JSE than their younger classmates [32].…”
Section: Discussionmentioning
confidence: 94%
“…While (32),found that increasing the age of Brazilian nurses had no effect on the level of their empathy.…”
Section: Discussionmentioning
confidence: 96%